Pengaruh hormon alami dan lama perendaman benih cabai merah (Capsicum annum L.) kedaluwarsa terhadap perkecambahan, pertumbuhan, dan produksinya - Noor Fitriya Mirta Liana; Syaiful Anwar; Florentina Kusmiyati (Jurnal Ilmiah Pertanian, 2022)
Red chili (Capsicum annum L.) is a vegetable that has high economic value. However, red chili production has decreased because of seed deterioration, such as expired seeds. Seed invigoration attempts to maintain seed germination ability when it has deteriorated. Extracts of onion and banana weevil can be used for invigoration. The research aimed to know the effect of various natural hormones, soaking time, and interaction of the two treatments of expired red chili seeds on germination, growth, and production. The research used a factorial, completely randomized design (CRD), which consisted of the type of natural hormones for soaking expired red chili seeds, aquadest as a control, onion extract 25%, banana weevil extract 25%, and onion extract 25% + banana weevil 25%; and soaking time for expired red chili seeds, i.e., 4 hours, 8 hours and 12 hours. Based on the result, The effect of soaking expired red chili seeds on natural hormones significantly impacted maximum growth potential, germination, growth rate, and simultaneous growth. Meanwhile, there were no significant effects on the vigor index, plant height, number of leaves, flowering age, harvest age, number of fruits per plant, fresh weight per plant, and fruit length. In addition, the treatment for a soaking time of expired red chili seeds for up to 12 hours had no significant effect on all observation parameters.